2017
DOI: 10.1111/tct.12655
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating on medication errors in nursing

Abstract: Four hospital-based simulations on select preventable medication errors were piloted with 72 undergraduate nursing students. The majority of students (60.8-84.1%) evaluated the experience positively with regards to time pressure, type/severity of events, challenges, and benefits for critical thinking and decision making regarding patient safety and medication errors. Four clinical simulation scenarios using high-fidelity patient simulators were developed focusing on select medication problems DISCUSSION: The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Millions of injuries and hundreds of thousands of deaths occur yearly in the United States from preventable errors 28,29. Many interventions have been implemented at the bedside; however, significant harm from preventable errors has continued at worrying rates 29-35. Although most interventions have been applied at the point of care, it has been suggested that the impetus of adverse events stems from factors at the system level, rather than isolated instances of human error 36,37.…”
Section: Application Of Within-methods Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Millions of injuries and hundreds of thousands of deaths occur yearly in the United States from preventable errors 28,29. Many interventions have been implemented at the bedside; however, significant harm from preventable errors has continued at worrying rates 29-35. Although most interventions have been applied at the point of care, it has been suggested that the impetus of adverse events stems from factors at the system level, rather than isolated instances of human error 36,37.…”
Section: Application Of Within-methods Data Analysismentioning
confidence: 99%
“…28,29 Many interventions have been implemented at the bedside; however, significant harm from preventable errors has continued at worrying rates. [29][30][31][32][33][34][35] Although most interventions have been applied at the point of care, it has been suggested that the impetus of adverse events stems from factors at the system level, rather than isolated instances of human error. 36,37 Of note, reports indicate that Magnet-designated hospitals have optimized nurse communication, reduced patient injuries, and 14% lower mortality rates compared with non-Magnet-designated facilities.…”
Section: Millions Of Injuries and Hundreds Of Thousands Of Deaths Occ...mentioning
confidence: 99%
“…The study of Marvanova and Henkel revealed that nurses had to have the knowledge and skills to manage drugs before they were hired for primary care or any medical services to prevent the mistakes of drug administration (8). Also, Darvishpour et al showed that the most important barriers for nurses in prescription were educational and human barriers as well as socio-cultural and organizational factors (9).…”
Section: Introductionmentioning
confidence: 99%
“…3(p1013) Nurses play a key role in identifying, reporting, and preventing medication errors because of their role in administering medications and monitoring patients' responses. 4 Most hospitals in the United States use incident reporting systems as tools for improving medication safety; however, incident reporting may not always provide actionable insights into conditions that contribute to errors. 5,6 Patient safety experts generally believe that medication errors occur because challenges in the sociotechnical work-system (interacting components, humans, organizations, technologies and tools, environments, and tasks) lead to problems with processes that influence outcomes of care.…”
mentioning
confidence: 99%
“…A medication error can be defined as “a failure in the treatment process that leads to, or has the potential to lead to, harm to the patient.”3 (p1013) Nurses play a key role in identifying, reporting, and preventing medication errors because of their role in administering medications and monitoring patients' responses 4. Most hospitals in the United States use incident reporting systems as tools for improving medication safety; however, incident reporting may not always provide actionable insights into conditions that contribute to errors 5,6…”
mentioning
confidence: 99%